Diagnosis and treatment of splenic torsion in children: preoperative thrombocytosis predicts splenic infarction - Zengmeng Wang; Chunhui Peng; Dongyang Wu; Kai Wang; Yajun Chen (BMC, 2022)
Abstract Background Pediatric splenic torsion is a rare entity, and the most common cause is wandering spleen. This study aimed to summarize our clinical experience in the diagnosis and surgical treatment pediatric patients with splenic torsion, and to use preoperative thrombocytosis as a preoperative predictive factor for splenic infarction. Methods From January 1st, 2016 to December 31st, 2021, 6 children diagnosed as splenic torsion were included. All patients were surgically treated and followed up. The clinical data was collected including clinical presentations, laboratory tests, imaging results, surgical procedures, and prognosis. Clinical experience of diagnosis and surgical treatment were summarized. Results There were 4 females and 2 males, with median age at surgery 102.6 (range 9.4-170.7) months. Abdominal pain and abdominal mass were the most common presentations. The diagnosis of splenic torsion depended on imaging studies, and adjacent organ involvement (gastric and pancreas torsion) was observed on contrast CT in one patient. Five patients were diagnosed as torsion of wandering spleen, and one was torsion of wandering accessory spleen. Emergent laparoscopic or open splenectomy was performed in all patients. Pathology revealed total splenic infarction in 4 patients, partial infarction in 1 patient, and viable spleen with congestion and hemorrhage in 1 patient. Preoperative platelet counts were elevated in all 4 patients with splenic infarction, but normal in the rest 2 with viable spleen. Postoperative transient portal vein branch thromboembolism occurred in one patient. Conclusions Imaging modalities are crucial for the diagnosis of pediatric splenic torsion and adjacent organ involvement. Preoperative thrombocytosis may predict splenic infarction. Spleen preserving surgery should be seriously considered over splenectomy in patients with a viable spleen.